2020
DOI: 10.1080/13668803.2020.1816901
|View full text |Cite
|
Sign up to set email alerts
|

How individual gender role beliefs, organizational gender norms, and national gender norms predict parents’ work-Family guilt in Europe

Abstract: The guilt that mothers feel about the time and energy that they invest in work instead of their family is often proposed to be an important reason for why mothers 'opt-out' the career track. We sought to understand if mothers indeed experience more workfamily guilt than fathers and how this relates to both their own gender role beliefs and organizational gender norms across nine European countries. Analyses draw on the European Social Workforce Survey, with data from 2619 working parents nested in 110 organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…IAT) of gender equality such as Hungary. Although a recent study indicated that while organizational cultures are predictive of fathers' and mothers' work–family guilt, national cultures are not (Aarntzen et al, 2021 ) therefore although, in need of further investigation, these studies may be generalizable to other countries.…”
Section: Discussionmentioning
confidence: 91%
“…IAT) of gender equality such as Hungary. Although a recent study indicated that while organizational cultures are predictive of fathers' and mothers' work–family guilt, national cultures are not (Aarntzen et al, 2021 ) therefore although, in need of further investigation, these studies may be generalizable to other countries.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, the study limited the assessment of WLB to one's own perception, which is likely to be one of the key causal factors within the study. Nevertheless, in future research, it would be interesting to examine other dimensions of WLB, and enlarge the spectrum of analysis, for example, to the emotional dimensions such as feelings of work-family guilt (Aarntzen et al, 2020(Aarntzen et al, , 2020Korabik, 2015). For instance, even when home responsibilities are shared between partners, gender role prescriptions may still cause guilt among women, when, for example, they feel they should spend more time with their children as prescribed by societal norms of motherhood (Meeussen & Van Laar, 2018;Newman & Henderson, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The present study further highlights the significant role of the spouse on the life satisfaction of parents struggling with strain-based WIF. Considering recent research suggesting that mothers experience more guilt due to the impact of their work on their family than fathers (Aarntzen et al, 2021 ; Borelli et al, 2017 ) and that four in five participants in the present study were mothers, the significant impact of spouse-child activities on participants’ life satisfaction is noteworthy. Furthermore, evidence exists supporting the importance of the source of support and its significance when occurring where it is perceived to be the most needed (French et al, 2018 ).…”
Section: Discussionmentioning
confidence: 49%
“…Recent research also suggests that organizations can help mothers who experience WFG by developing more egalitarian organizational norms (Aarntzen et al, 2021 ). This could be encouraged by ensuring that organizations present adequate work-family policies (e.g., flexible hours) that apply and are used by both fathers and mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation